Warm-based basal sediment entrainment and far-field Pleistocene origin evidenced in central Transantarctic blue ice through stable isotopes and internal structures - Graly, Joseph A.; Licht, Kathy J.; Kassab, Christine M.; Bird, Broxton W.; Kaplan, Michael R. (Cambridge University Press, 2018)
Stable isotopes of water (δ18O and δ2H) were measured in the debris-laden ice underlying an Antarctic blue ice moraine, and in adjoining Law Glacier in the central Transantarctic Mountains. Air bubble content and morphology were assessed in shallow ice core samples. Stable isotope measurements plot either on the meteoric waterline or are enriched from it. The data cluster in two groups: the ice underlying the moraine has a δ2H:δ18O slope of 5.35 ± 0.92; ice from adjoining portions of Law Glacier has a slope of 6.69 ± 1.39. This enrichment pattern suggests the moraine's underlying blue ice entrained sediment through refreezing processes acting in an open system. Glaciological conditions favorable to warm-based sediment entrainment occur 30–50 km upstream. Basal melting and refreezing are further evidenced by abundant vapor figures formed from internal melting of the ice crystals. Both the moraine ice and Law Glacier are sufficiently depleted of heavy isotopes that their ice cannot be sourced locally, but instead must be derived from far-field interior regions of the higher polar plateau. Modeled ice flow speeds suggest the ice must be at least 80 ka old, with Law Glacier's ice possibly dating to OIS 5 and moraine ice older still.